Lifetime mortality associated with hypertrophic cardiomyopathy: 28-year outcome of an historical cohort. (25th November 2020) - Maurizi, N; Cecchi, F; Tomberli, F; Baldini, K; Fumagalli, F; Bonacchi, G; Marchionni, N; Maron, B.J; Olivotto, I
Abstract: Background: Current understanding of the lifetime mortality of patients with hypertrophic cardiomyopathy (HCM) has been extrapolated from cohorts with 8–10 years follow-up. Real survival rates and long-term burden of HCM are largely unresolved. Objective: To describe HCM lifetime mortality over 28-years of observation. Methods: We analyzed clinical/instrumental data of the historic cohort of 202 patients diagnosed from 1970s. ECG, echocardiographic, clinical records until last follow-up were recorded. Reasons for death were classified as HCM related (Sudden Death (SD), Heart Failure related (HF)) and non-HCM related deaths. Results: Patients were followed-up for 28±6 years (41±17 to 69±14 years), 63% were males. Patients progressively dilated the Left Atrium (40±6 to 50±9mm, p<0.01), depressed ejection fraction (65±9 to 54±12, p<0.01), developed diastolic restrictive pattern and decreased LV wall thickness (23±5 to 19±4mm, p<0.01). One-hundred-eighteen deaths occurred at 66±12 years. HCM accounted for 69 deaths, 53 due to HF-related complications and 16 for SD. Annual HCM mortality rate increased from 0.6% at 10 years following diagnosis to 1.4% during 11–28 years of follow-up (p<0.01): HF yearly burden increased from 0.6% to 1.3%, p<0.01, SD remained similar in the two periods (0.1%, 0.4% respectively). Conclusions: HCM-related mortality at 10 years significantly underestimated the lifetime rates of HF death, which doubled in the second/third decade of observation. Conversely, SD rates remained constantly low. Real burden of HCM is time dependent and can be appreciated only after prolonged exposure to the disease. Funding Acknowledgement: Type of funding source: None